A Socio-Political Approach to Modernist Architecture in Soviet Lithuania (KULT_online, 2019)
The book Baltic Modernism. Architecture and Housing in Soviet Lithuania is a detailed analysis of the characteristics of modernist architecture in Soviet Lithuania. It emphasizes the close relationship between the architectural community in Lithuania and the historical, urban, and ethnic heritage as well as the national landscape. Starting from a broad discussion of Soviet Modernism, the author zooms in on specific aspects: industrialization, urban and rural planning, housing, and the consumer-cultural network. The buildings and urban structures are analyzed using a socio-political approach pointing to tensions between standardization and customization. The book is an important source for historians of architecture as well as for interdisciplinary research in cultural, history, urban studies and sociology of architecture.